Particleboard from plantation species of Neolamarckia Cadamba Sp.(Kelempayan) and Endospermum Diadenum Sp. (Sesenduk) - Sadam Kahar (2018)
The objectives of this study were to evaluate the mechanical and physical properties of particleboard made from the wood of Neolamarckia Cadamba sp. (NC) and Endospermum Diadenum sp. (ED) using urea formaldehyde as a binder. The NC and ED wood species are one of the selected forest plantation in Malaysia due to fast-growing species. Also known as lesser-known commercial timbers (LKCT) species. The panels were manufactured using 8%, 10% and 12% of Urea Formaldehyde with wood ratio 1:0, 0:1, 1:1, 3:2 and 7:3 of NC: ED. The modulus of rupture (MOR), modulus of elasticity (MOE), internal bonding strength (IB), density and moisture content, water absorption (WA) and thickness swelling (TS) were evaluated based on British European standard. The sample was characterized for the physical characteristics by determining the surface morphology using field emission scanning electron microscopy (FESEM), energy- disperse x-ray spectroscopy (EDX) analysis and surface functional group analysis chemistry (FT-IR). Overall the results showed the specimens made from species 7:3 ratio of NC:ED at 12% resin content had the highest MOE and MOR values compared to 1:1, and 3:2 of NC:ED. The values of MOE and MOR were 29.18 and 3669.67 MPa, respectively. Whereas the highest values was from 7:3 ratio of NC:ED compared to 1:0, 1:1 and 3:2 of NC:ED. The values of IB 1.34 MPa. The highest values of WA and TS were 67.45 and 17.38%, respectively. The mechanical and physical properties of particleboards produced gradually improved the strength properties with increased the amount of NC wood species and resin content. Based on these findings in this work Neolamarckia cadamba sp. and Endorspermum diadenum sp. had potential to be used as raw material to produce particleboard panel.